New species in Italy - Barbato F.; Corbari L. (Aspects économiques de la production aquacole, 1995)
This work considers the species of marine teleosts not yet established with relevant productions, reared in Italy at various levels, from research, through pilot scale to commercial scale. For each species a short note is reported considering the main characteristics of interest for rearing and for market perspectives.
Seminar of the CIHEAM Network on Socio-economic and Legal Aspects of Aquaculture in the Mediterranean (SELAM), 1995/05/17-19, Montpellier (France)